Assimilation of volcanic sulfur dioxide products from IASI and TROPOMI into the chemical transport model MOCAGE: case study of the 2021 La Soufrière Saint Vincent eruption with the March 2022 version of MOCAGE - M. Bacles; J. Améric; V. Guidard (Atmospheric Measurement Techniques)
Sulfur dioxide emitted during volcanic eruptions can be hazardous for aviation safety. As part of their activities, the Volcanic Ash Advisory Centres (VAACs) are therefore interested in the real-time atmospheric monitoring of this gas. A recent development aims at improving the forecasts of volcanic sulfur dioxide quantities made by the MOCAGE (Modèle de Chimie Atmosphérique à Grande Échelle) chemistry transport model. For this purpose, observations from both TROPOMI (Tropospheric Monitoring Instrument) and IASI (Infrared Atmospheric Sounding Interferometer; B and C) located on separate polar-orbiting satellites are assimilated into the model. These sulfur dioxide measurements are based on the eruption event of the La Soufrière Saint Vincent volcano in April 2021. Observations from OMI (Ozone Monitoring Instrument) are considered validation data. The resulting assimilation experiments show that the combined assimilation of IASI and TROPOMI observations always leads to a better forecast compared to the independent assimilation of data from each instrument. Sulfur dioxide atmospheric field forecasts are better when the available observations are numerous and cover a long time window.